TRANSFORMASI DIGITAL DALAM PERPAJAKAN: PELATIHAN CORETAX UNTUK MENINGKATKAN KEPATUHAN PAJAK - Laili, Nur Isra; Saputra , Muhammad Dio; Sarmini , Sarmini (PUAN INDONESIA, 2025)
This community service program aims to improve digital tax literacy and tax compliance at Sekolah Nabila through training on the use of the Coretax application. The activity addresses challenges in digital tax administration, such as low digital literacy and the lack of training on Coretax usage. The training covers basic tax introduction, how to operate Coretax, and simulations of electronic tax reporting. The results of the program show that more than 75% of participants successfully operated the application and submitted their tax reports electronically. In addition, participants' awareness of the importance of tax compliance also increased significantly. This program has had a positive impact on enhancing participants' technical skills in managing their tax administration. With improved digital literacy and tax awareness, participants are expected to become more independent in fulfilling their tax obligations while reducing the risk of administrative errors that could lead to tax penalties. This program also serves as a model for other communities facing similar challenges in adopting digital taxation systems.